From Tobacco Cigarettes to Electronic Cigarettes: The Two Sides of a Nicotine Coin - Ahmad Besaratinia (Frontiers Media S.A., 2021)
Tobacco smoking-related diseases, including cardiovascular disease, pulmonary disease, stroke, and cancer in multiple organ sites, are the leading causes of preventable death, worldwide. Youth electronic cigarette use (vaping) is an evolving public health problem in the United States and around the world. Many of the same toxicants and carcinogens present in tobacco smoke are also found in electronic cigarette vapor, although mostly at substantially lower levels. The reduced concentrations of these chemicals in electronic cigarette vapor may imply lower health risk; however, they cannot equate to no risk. To date, the long-term health consequences of vaping are largely unknown. This "Perspective" provides a concise chronology of events leading up to an unprecedented global challenge, namely the convergence of global tobacco epidemic and youth vaping epidemic. Current state of knowledge, outstanding questions in the field, present challenges, and future directions in research are highlighted. The existing data show a continued and dynamic evolution of the converged epidemics. The goal should be to prevent youth vaping while improving smoking cessation strategies. In smokers who are unable or unwilling to quit smoking, the objective should be to provide "provably" safe or less-harmful alternatives, which should "completely" or "substantially" substitute tobacco cigarettes.